Variación de biomasa aérea y densidad de madera en un bosque de colina baja, distritos Napo/Mazán, Loreto. 2023 - Cisneros Bazan, Emanuel (2024)
The present study on the variation of aboveground biomass and wood density was conducted in the low hill forest of the Napo/Mazán districts, under concession contracts N° 16-LOR-MAY/CON-MAD-2018-005 and 16-LOR-MAY/CON-MAD 2018-008. The results of the inventory reveal a remarkable diversity, with 58 species, 24 families and 48 genera, highlighting Virolla mollissima as the dominant species with 993 trees (25.4%) and Myristicaceae as the most abundant family, with a total of 1206 trees. The model of Chave et al., (2014) is identified as the most accurate option to estimate aboveground biomass, given its high coefficient of determination (R² = 0.878) and a standard error of estimation (SEE) of 23.11%. A total aboveground biomass of 9290.08 kg/ha was calculated for the area under study, with Eschweilera albiflora being the species that contributes the highest amount of aboveground biomass, with 1554.23 kg/ha, followed by Virola mollissima, which contributes 1209.48 kg/ha. Also, a weak correlation (0.181) was found between biomass and wood density, according to Spearman's Rho correlation test. This suggests that, although there is a relationship, it is relatively low, indicating that other factors could influence the growth and development of tree species. Finally, the research hypothesis is accepted, which establishes that there are variations in aerial biomass and wood density among the different tree species in the low hill forest, linked to the ecological characteristics of each species, their adaptation to environmental conditions and their stage of development.